THE PHENOMENON OF CROSS-REACTIVITY IN PATIENTS WITH RESPIRATORY ALLERGIES - Irsaliyeva Fatima Khusnutdinovna; Nizamov Kutpiddin Fatkhullaevich (Scholar Express Journals, 2026)
According to clinical studies, 20 to 45% of patients with pollinosis are sensitized to several related products and fruits. Oral allergy syndrome (swelling and itching of the oral mucosa that came into contact with food – lips, tongue, pharynx, palate) occurred during the plant flowering season when patients consumed raw fruits. In this regard, understanding the mechanisms of sensitization to homologous allergens allows for optimizing methods of diagnosing food allergies in patients with pollinosis. The choice of diagnostic methods used is fundamentally important for verifying crosssensitization in patients with pollinosis. The use of the "double-prick test" with fresh fruits and vegetables is a more sensitive method for studying reactivity to labile allergens.
Keywords: Cross-allergy; respiratory allergies; pollinosis